Peningkatan Kepuasan Masyarakat melalui Peran Program Pemeliharaan Pegawai dan Kepuasan Kerja - Khuzaini . Khuzaini; Ervica - Jamilah; Lamsah . Lamsah; Basuki . Basuki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
The role essential of functions of human resource management is to take care of maintance employees. The process is normally divided into two categories: first category includes different activities such as having health and safety in working centers, performing healthy and sport programs and some other similar activities to save and improve employees' physical characteristics. The second group includes other important issues normally called benefit programs, which includes good health insurance and retiring plans. Whenever an organization provides good benefit programs and supporting programs, there is a better job satisfaction among employee. This study try to find out about, the effects of related services to support employee to reach job satisfaction and employee activities in public sectors in Banjarmasin City is used 126 random samples. The results show that employees are relatively satisfied from the benefit programs of the public organization and they were relatively happy on working for such organization.